Comparison of arch bar removal with and without the usage of local anaesthesia. - P. DEEKSHEETHA,; BALAKRISHNA R N,; KAREEM, NASHRA (The journal of contemporary issues in business and government, 2020)
The aim of this study is to assess the arch for removal With local anaesthesia versus arch bar removal without anaesthesia. Intermaxillary fixation is the most commonly used treatment modality In patients with maxillofacial trauma. On removal of the IMFs General anaesthesia and various forms of local anaesthesia and local anaesthetic techniques in the form of infiltrations, nerve blocks, topical local anaesthetic spray, topical local anaesthetic gel.This was a University- based study. The data was obtained by reviewing case sheets of patients from June 2019 to March 2020. The case sheets of the patients who had undergone intermaxillary fixation were appraised to assess if the arch bars were removed using local anaesthesia or without the usage of a local anaesthetic agent. 97% of the patients were given local anaesthesia for the removal of the arch bars. Lignocaine with adrenaline was the most commonly used (96%) local anaesthetic solution. 2ML of the local anaesthetic solution was the common amount of local anaesthetic solution used (35%)